Colisão de direitos: a liberdade religiosa e a liberdade de expressão na esfera pública à luz da constituição - Rosim, Arnaldo Ricardo (2014)
This essay is about the collision of rights involving the freedom of religions and the freedom of expression in the public square. This work aims to reveal witch of the two fundamental rights should prevail in case of conflict between the freedoms occurring in the public sphere and what its extension, on previously specified hypoyhesis. Intends to find the constitutionally optimal solution to the conflict between these rights, throught the use of techniques provided to the constitutional doctrine